The employment of recommended root canal treatment procedures by dentists in Croatia and the Czech Republic - Kapitán, Martin; Schmidt, Jan; Vavřičková, Lenka; Vidović Zdrilić, Ivana; Vidas Hrstić, Jelena (International endodontic journal, 2025)
AIM: This study aimed to evaluate the compliance of dentists in Croatia and the Czech Republic with endodontic recommendations and identify the subjective and objective factors influencing their adherence to them. METHODOLOGY: A total of 1386 dentists from Croatia and the Czech Republic participated in an online survey through a self-administered, author-designed questionnaire. After excluding those who did not perform root canal treatments (RCT), 1376 responses (394 from Croatia and 982 from the Czech Republic) were statistically analysed. RESULTS: The median age of respondents was 40 years, with a higher proportion of females in both countries. Croatian dentists treated fewer patients weekly but performed more RCTs and placed more composite fillings than their Czech counterparts. Czech dentists more frequently employed magnification devices, rubber dam (RD), pre-endodontic build-ups, nickel-titanium (NiTi) instruments, irrigant activation, bioceramic sealers, indirect post-endodontic restoration of lateral teeth, and single-visit treatments. These practices were also more common among endodontists than general dental practitioners and other specialists in both countries. Croatian dentists adhered more consistently to the recommended irrigation protocol. In the Czech group, adherence to recommended procedures, such as magnification, RD usage, and irrigation protocol correlated with younger age, smaller weekly number of patients, and preference for treating patients in the supine position. No such correlations were observed among the Croatian dentists. CONCLUSIONS: Despite notable improvements in recent years, dentists still do not fully comply with the recommended RCT working procedures in Croatia and the Czech Republic.
Keywords: terapie kořenového kanálku; dodržování směrnic; Male; Female; Humans; lidé středního věku; mužské pohlaví; dospělí; lidé; Surveys and Questionnaires; průzkumy a dotazníky; Česká republika; ženské pohlaví; Czech Republic; Croatia; Dentists; vzorové postupy ve stomatologii; Root Canal Therapy; Chorvatsko; Adult; Guideline Adherence; Practice Patterns, Dentists'; zubní lékaři; Middle Aged